1992
DOI: 10.1007/bf02631062
|View full text |Cite
|
Sign up to set email alerts
|

A transformed human epithelial cell line that retains tight junctions post crisis

Abstract: The successful establishment of a postcrisis SV-40 T antigen transformed epithelial cell line, 1HAEo-, which retains tight junctions and vectorial ion transport, is described. Immunocytochemical analysis of 1HAEo- cells shows a defined pattern of cytokeratin staining and a characteristic pericellular localization of the adhesion molecule cellCAM 120/80, indicating the presence of junctional complexes. The presence of both tight junctions and desmosomes has been confirmed by electron microscopy. Cell monolayers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 55 publications
1
68
0
Order By: Relevance
“…16-HBE, an immortalised normal bronchial epithelial cell line (Cozens et al 1992), RPMI 2650a, a nasal epithelial cell line (Pace et al 2012a), and a mucin-producing human NCI-H292 airway epithelial cell line (Nogawa et al 2009) were used in this study.…”
Section: Stimulation Of Epithelial Cell Linesmentioning
confidence: 99%
“…16-HBE, an immortalised normal bronchial epithelial cell line (Cozens et al 1992), RPMI 2650a, a nasal epithelial cell line (Pace et al 2012a), and a mucin-producing human NCI-H292 airway epithelial cell line (Nogawa et al 2009) were used in this study.…”
Section: Stimulation Of Epithelial Cell Linesmentioning
confidence: 99%
“…We have compared the ability of three forms of PEI to deliver a reporter gene to a human bronchial epithelial cell line (16HBE) as a model for airway gene delivery under different culture conditions (subconfluent, confluent and polarized). 21,22 We have shown that all three forms of PEI gave significantly better reporter gene delivery compared to using liposomes. Linear 22 kDa PEI was significantly better than branched 25 or 50 kDa PEI.…”
Section: Introductionmentioning
confidence: 95%
“…The variation in response in the pT10CFTR2-treated animals meant that the average genistein response was not significantly different from the CF mice treated with the control plasmid pT10. If it is assumed, however, that the lack of a genistein response reflects a failure of gene delivery and these 'failures' are excluded, then the mean genistein response after L- 22 …”
Section: Pei-mediated Gene Delivery Jw Wiseman Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…We have used a human bronchial epithelial cell line (16HBE) as a model for airway gene delivery under several different culture conditions including sub-confluent, confluent and polarized. 15,16 We have shown significant enhancement of reporter gene delivery in each of these cell culture conditions using ␀-estradiol or methyl-prednisolone. The order in which steroid is combined in the complex is important.…”
Section: Introductionmentioning
confidence: 98%